Progress in Medicinal Chemistry Volume 52 - Lawton, G.; Lawton, G.; Witty, D.R. (Elsevier Science, 2013)
Progress in Medicinal Chemistry provides a review of eclectic developments in medicinal chemistry. This volume continues in the serial's tradition of providing an insight into the skills required of the modern medicinal chemist; in particular, the use of an appropriate selection of the wide range of tools now available to solve key scientific problems. Progress in Medicinal Chemistry provides a review of eclectic developments in medicinal chemistry. This volume continues in the serial's tradition of providing an insight into the skills required of the modern medicinal chemist; in particular, the use of an appropriate selection of the wide range of tools now available to solve key scientific problems.